Social causes of emotional divorce between spouses: Afield study from the wives' point of view - Abdullatif, Hadeel Farhan; Ali, Parween Hussein (Al-Adab Journal, 2023)
The new family manifested the problem of emotional divorce between couples which flows into the core of the marital life leaving bad effect on the family and the future of the couples and their children. It is one of the most overlooked problems in the Arabic societies in general, and the Iraqi society in particular to keep the children or to keep the social status. Hence, the study tackles the emotional divorce to identify its indications and causes, in addition to diagnosing the projection of these social problems on the couple and their children, revealing the relationship between emotional divorce and actual one, and reaching some solutions or suggestions to decrease or eliminate the problem between couples. To achieve the aims of the study, the researcher chooses a sample of (240) wives and it is represented by the stratified random sample which reflected the features of the study community which is the community of Baghdad with its two sides Al kharch (Al Mansour, Shuhada'a Al Baya'a, Al Shurta Al Raba'a) and Al Rasafa (Shari Filistine and Hay Al Ameen). This study is descriptive which relies on two approaches, the first is the social survey and the second is the comparative approach. The study relies on the questionnaire as the main tool in collecting data after going through many stages to verify its consistency and validity, in addition to utilizing simple observation and interviews, the data of questionnaires were processed statistically via the (SPSS) via using many statistical tools like (percentage principle, arithmetic mean, standard deviation, chi - square test, Steven Sampson's principle Pearson principle) Of the most important findings of the study are as follows, that the majority of wives in the sample suffer from the coldness of the relationship, and they consider the silence of the husband in the house a sign of an emotional divorce, what causes the husband's silence is caused by his preoccupation with moder.